TRANSFORMASI MANAJEMEN SEKOLAH MENUJU MODEL KOLABORATIF: MEMBANGUN BUDAYA ORGANISASI PARTISIPATIF UNTUK OPTIMALISASI PENGEMBANGAN KURIKULUM - Putra, Rohid Refaldo Syah (STKIP Pesisir Selatan, 2025)
The transformation of school management towards a collaborative model grounded in participatory organizational culture is essential to address the challenges of developing relevant and adaptive curricula in modern education. The prevailing centralized management patterns in Indonesian schools limit the participation of school members in curriculum decision-making, resulting in curricula that are less contextual and do not fully meet students’ need. This study applies a qualitative approach using literature review and descriptive-analytical methods to examine various theoretical and empirical studies. The findings indicate that implementing participatory culture, collaborative leadership, open communication, continuous training, and a consistent culture of evaluation and improvement are fundamental to creating a responsive curriculum. Schools adopting participatory management are proven to be more adaptive to change, enhance a sense of ownership, and strengthen collaboration among all school components. The study concludes that transforming organizational culture towards a participatory model is a key strategy for developing contextual, effective, and sustainable curricula, and is capable of improving the overall quality of education.